The impact of aquatic based plyometric training on jump performance: A critical review - Mullenax, P. M.; Johnson, Q.; Trevino, M. A.; Smith, D. B.; Jacobson, B. H.; Dawes, J. J. (International Journal of Exercise Science, 2021)
There is evidence to suggest that aquatic plyometric training (APT) may be an effective and safer alternative to traditional land-based plyometric training (LPT) when training to increase jump performance. The aim of this review was to critically examine the current literature regarding the effects of APT vs. LPT on jump performance in athletic populations. Key terms were employed in five separate databases to complete the current review. Available articles were screened for inclusion and exclusion criteria to determine which studies were deemed eligible for review. Outcome measure in these studies included those assessing lower extremity power and jump performance (i.e., drop jumps, broad jumps, sergeant jumps, repeated countermovement jumps, and vertical jumps). All but one of the studies included in this critical review showed significant improvements in jump performance after LPT and APT interventions. Both LPT and APT groups experienced similar increases in jump performance and lower-body power, pre- to post-test, in the majority of the studies examined in this review. LPT and APT have the ability to improve lower extremity explosive strength and jump performance within athletic populations. Improvements in lower body power may improve overall athletic performance. Observations from this review may be used by sport coaches, strength coaches, and athletes alike to weigh the pros and cons of both forms of plyometric training. Observations from this review may also be used to weigh the pros and cons of APT over LPT in terms of reducing risk of injury.